Determinants of depression among undergraduate medical students of a private medical college in Lahore - Uzma Zafar; Seema Daud; Attiqa Khalid (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the prevalence and determinants of depression in undergraduate medical students within their learning environment. Methods: The descriptive cross-sectional study was conducted at the Lahore Medical and Dental College, Lahore, Pakistan, from May to June 2015, and comprised medical students of all the five professional years. A structured questionnaire was used to collect data. Section one of the questionnaire related to demographic information, section two comprised Patient health questionnaire-9 for screening depression, and section three was the Dundee ready education environment measure inventory to gather students’ perceptions of their learning environment. Data was analysed using SPSS 22. Results: Of the 533 students, 206(39%) were males, 327(61%) were females, 213(40%) were of preclinical years and 320(60%) were of clinical academic years. Overall, 399(75%) students were found to be depressed. Of them, 255(64%) were females and 144(36%) were males. Among the students, 96(18%) had negative perception of their learning environment, and out of these, 91(95%) were found to be depressed. There was significant association of depression with female gender (p=0.037) and negative perception of the students of their learning climate (p<0.001). Conclusion: The prevalence of depression was found to be high among the medical students and it was associated with female gender and negative perception of the learning environment. Keywords: Patient health questionnaire-9, Depressive symptoms, Environmental determinants, DREEM inventory